How have formal firms recovered from the pandemic? Insights from survey and tax administrative data in Zambia - Christopher Hoy; Laban Simbeye; Muhammad Abdullah Ali Malik; Aliisa Koivisto; Mashekwa Maboshe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper examines how formal firms have been impacted by and recovered from the pandemic by drawing on two distinct but complementary data sources. This is the first attempt to use both survey and tax administrative data to measure the initial decline and subsequent recovery of firm sales and employment in a low- or lower-middle-income country. Specifically, the findings of three rounds of follow-up surveys to a standard World Bank Enterprise Survey completed immediately prior to the pandemic are compared to information contained in the universe of value added tax and personal income tax returns filed by firms during 2020 and the first half of 2021 in Zambia. Despite substantial differences in terms of the breadth and depth of these data sources, they show a very similar pattern. Sales by formal firms recovered from the pandemic far more strongly than their employment levels. By July 2021, both the survey and tax administrative data show that most firms experienced a complete recovery in sales, while levels of employment worsened over the course of the pandemic for many firms. Two key insights emerge from this analysis. First, formal firms appear to have adjusted their operations in a way that reduced their need for as much labour to achieve the same (or higher) levels of sales. Second, if formal firms' reduced reliance on labour persists, lower levels of formal employment in low- and middle-income countries may be a concerning consequence of the COVID-19 pandemic that lingers for years to come.
Keywords: D22; J21; J23; O12; 330; firms; COVID-19; tax administrative data; Zambia; economic recovery